Proceedings of the 20th International ACM SIGACCESS Conference on Computers and Accessibility 2018
DOI: 10.1145/3234695.3236364
|View full text |Cite
|
Sign up to set email alerts
|

Examining Image-Based Button Labeling for Accessibility in Android Apps through Large-Scale Analysis

Abstract: of their abilities or use of assistive technologies. However, prior work has shown there still exist important accessibility barriers within apps [20,21,37,40,42,43]. Awareness of the need to create more accessible apps is increasing. Google and Apple are the primary organizations that facilitate mobile technology and the app marketplace, through the Android and iOS platforms. Both have released developer and design guidelines for accessibility [16,30], provide accessibility services as part of their platforms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The review found no author or journal with extensive publication in the field of the accessible addressing app mobile and websites, despite the increasing number of articles published in high-impact journals within the tourism field that have taken an interest in the topic. Therefore, other studies on websites [58] and mobile applications in other sectors have been taken into account [59][60][61][62][63][64]. No similar studies have been found directly related to Spain and Portugal.…”
Section: Discussionmentioning
confidence: 98%
“…The review found no author or journal with extensive publication in the field of the accessible addressing app mobile and websites, despite the increasing number of articles published in high-impact journals within the tourism field that have taken an interest in the topic. Therefore, other studies on websites [58] and mobile applications in other sectors have been taken into account [59][60][61][62][63][64]. No similar studies have been found directly related to Spain and Portugal.…”
Section: Discussionmentioning
confidence: 98%
“…These technologies depend heavily on the availability of accessibility metadata provided by developers to expose the underlying semantics of apps [2,37]. [65][66][67], and our analysis in this paper (Section 3.3), show that developers routinely fail to include this information, and many mobile apps remain inaccessible.…”
Section: Supporting Mobile Accessibilitymentioning
confidence: 99%
“…within the accessibility research community rather than software engineering. This research area involves studying certain categories of websites (e.g., airline websites [31], [32], education portals [33], other categories [34], [35], [36], [37]) or certain platforms (e.g., Android [38], [39], [40]), and then focusing on manually observing how non-sighted users would use those apps or websites in order to identify any patterns or trends in accessibility, with the purpose of publishing improved accessibility guidelines. Another line of work focuses on researching software development best practices and how do they impact the accessibility of the end product.…”
Section: Accessibility Guidelines the Majority Of Existing Work Liesmentioning
confidence: 99%